A rare case of calvarial tuberculosis in post-COVID-19 scenario - Abhijit Acharya; Atmaranjan Dash; Sarita Otta (International Journal of Mycobacteriology, 2022)
Isolated calvarial involvement with tuberculosis (TB) is a very rare entity, with the incidence of only 0.01% of all patients with mycobacterial infections. The factors attributable could be malnutrition, poor socioeconomic conditions, and immunodeficiency syndromes. We hereby present the case of a 35-year-old male who had recently recovered from coronavirus disease 2019 and a diagnosed case of Evan's syndrome with secondary hemophagocytic lymphohistiocytosis who presented with a scalp swelling on the right frontotemporal region. He presented to the emergency department with acute-onset generalized tonic − clonic seizures with high-grade fever. Clinically, the swelling appeared like a cystic swelling of the scalp. On evaluation, there was a collection present below the scalp communicating with the extradural space, involving the underlying skull bone. The patient was operated with drainage of the abscess plus excision of the pathological underlying skull bone. The pus revealed florid amount of acid-fast bacillus on Ziehl–Neelsen staining. The patient was started on four drugs Category 1 antitubercular regimen. The patient responded well to the combined surgical and medical treatment. It should be emphasized that TB can involve any part of the body. It should be kept as differential diagnosis of any chronic inflammatory lesion involving the bony skeleton, especially in endemic countries where combined surgical and medical treatment is usually sufficient to provide a cure.